Multigenic Disease and Bilineal Inheritance in Dilated Cardiomyopathy Is Illustrated in Nonsegregating LMNA Pedigrees. (July 2018) - Cowan, Jason R.; Kinnamon, Daniel D.; Morales, Ana; Salyer, Lorien; Nickerson, Deborah A.; Hershberger, Ray E.
Abstract : Background: We have previously described 19 pedigrees with apparent lamin ( LMNA )-related dilated cardiomyopathy (DCM) manifesting in affected family members across multiple generations. In 6 of 19 families, at least 1 individual with idiopathic DCM did not carry the family's LMNA variant. We hypothesized that additional genetic cause may underlie DCM in these families. Methods: Affected family members underwent exome sequencing to identify additional genetic cause of DCM in the 6 families with nonsegregating LMNA variants. Results: In 5 of 6 pedigrees, we identified at least 1 additional rare variant in a known DCM gene that could plausibly contribute to disease in the LMNA variant-negative individuals. Bilineal inheritance was clear or presumed to be present in 3 of 5 families and was possible in the remaining 2. At least 1 individual with a LMNA variant also carried a variant in an additional identified DCM gene in each family. Using a multivariate linear mixed model for quantitative traits, we demonstrated that the presence of these additional variants was associated with a more severe phenotype after adjusting for sex, age, and the presence/absence of the family's nonsegregating LMNA variant. Conclusions: Our data support DCM as a genetically heterogeneous disease with, at times, multigene causation. Although the frequency of DCM resulting from multigenic cause is uncertain, our data suggest it may be higher than previously anticipated. Abstract : Supplemental Digital Content is available in the text.